(untitled) (Principles of Medical Toxicology, 2025)
Author Dr. Shannumukha Sainath A, Assistant Professor, Department of Pharmacy Practice, Nirmala College of Pharmacy, Ukkayapalli, Kadapa, Andhra Pradesh, India Abstract Managing toxic emergencies requires a systematic approach beginning with rapid stabilization followed by specific interventions. Initial management follows the ABCDE (Airway, Breathing, Circulation, Disability, Exposure) framework, with particular attention to securing compromised airways, supporting ventilation, establishing vascular access, and addressing life-threatening dysrhythmias or hypotension. Simultaneously, attempts to identify the toxin involve examining vital sign patterns, recognizing toxidromes, and gathering exposure history from patients, bystanders, or prehospital personnel. Critical care management addresses organ system complications including hepatotoxicity, nephrotoxicity, cardiotoxicity, neurotoxicity, and metabolic disturbances. Targeted interventions for specific toxins are initiated while monitoring progresses from basic vital signs to advanced parameters including continuous ECG, capnography, invasive hemodynamic measurements, and serial laboratory studies tailored to the suspected agent. Particular toxins require specialized monitoring such as QRS duration in sodium channel blocker toxicity or anion gap in toxic alcohol ingestions. Comprehensive documentation encompasses initial presentation, interventions, response to treatment, consultation with poison centers or toxicologists, laboratory and diagnostic findings, and disposition decisions. This structured approach optimizes outcomes in poisoned patients while facilitating continuity of care, quality improvement, risk management, and potential medicolegal review. Keywords: Toxidromes, Critical Care, Antidotal Therapy, Toxicological Monitoring, Airway Management, Toxicology VIEW PDF